Faktor–Faktor Yang Memengaruhi Kinerja Usaha Pelaku Usaha Tempe Kampung Rawa Jakarta Pusat - Yunitasari, Ani; Nurmalina, Rita (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2024)
Entrepreneurship is closely related to the development of Small and Medium Enterprises (SMEs), including SMEs processing soybeans into tempeh. Tempeh is a source of protein that is popular with people because it is cheap. However, it cannot be denied that fluctuations in the price of imported soybeans, limited capital and simple technology are still problems for tempe business players. This research aims to analyze the factors that influence the business performance of tempe entrepreneurs in Kampung Rawa, Central Jakarta. This research was analyzed descriptively and using SEM-PLS analysis using a purposive sampling technique and 40 respondents. The results of the analysis show that individual factors and environmental factors directly influence entrepreneurial behavior. Then, business performance is directly influenced by entrepreneurial behavior and environmental factors, and indirectly influenced by individual factors and environmental factors through entrepreneurial behavior. Based on the results of the study, tempe business actors can increase their motivation to produce tempeh, carry out brand innovation as a form of branding and innovate as healthy tempeh so that it becomes an advantage compared to other tempe products